Neutrophil extracellular traps and fibrocytes in ST-segment elevation myocardial infarction - Hofbauer, Thomas M.; Mangold, Andreas; Scherz, Thomas; Seidl, Veronika; Panzenböck, Adelheid; Ondracek, Anna S.; Müller, Julian; Schneider, Matthias; Binder, Thomas; Hell, Lena; Lang, Irene M. (Basic research in cardiology, 2019)
Leukocyte-mediated inflammation is central in atherothrombosis and ST-segment elevation myocardial infarction (STEMI). Neutrophil extracellular traps (NETs) have been shown to enhance atherothrombosis and stimulate fibroblast function. We analyzed the effects of NETs on cardiac remodeling after STEMI. We measured double-stranded (ds)DNA and citrullinated histone H3 (citH3) as NET surrogate markers in human culprit site and femoral blood collected during primary percutaneous coronary intervention ( n = 50). Fibrocytes were characterized in whole blood by flow cytometry, and in culprit site thrombi and myocardium by immunofluorescence. To investigate mechanisms of fibrocyte activation, isolated NETs were used to induce fibrocyte responses in vitro. Enzymatic infarct size was assessed using creatine-phosphokinase isoform MB area under the curve. Left ventricular function was measured by transthoracic echocardiography. NET surrogate markers were increased at the culprit site compared to the femoral site and were positively correlated with infarct size and left ventricular dysfunction at follow-up. In vitro, NETs promoted fibrocyte differentiation from monocytes and induced fibrocyte activation. Highly activated fibrocytes accumulated at the culprit site and in the infarct transition zone. Our data suggest that NETs might be important mediators of fibrotic remodeling after STEMI, possibly by stimulating fibrocytes.